Can serum orexin levels be used as a marker in childhood epilepsy? - Mutluay Arslan; Canan Üstün; Ayşe Nur Coşkun; Hasan Çelik; Hacı Nadir Yalçın; Eda Karaismailoğlu; Erdim Sertoğlu; Bülent Ünay (Heliyon)
Objective: Epilepsy is one of the most common neurological diseases in the pediatric population. Orexins are excitatory peptides and associated with energy homeostasis, eating and drinking behaviors, sleep regulation, sleep-wake periods, analgesia, and cognitive activities such as attention, learning, and memory. The aim of this study was to reveal the relationship between plasma orexin levels and seizures in pediatric epilepsy patients with seizures, epilepsy patients in remission, and healthy control group with similar demographic characteristics. Material and methods: The study was conducted between December 2021 and December 2022 in the Department of Pediatric Neurology of a tertiary hospital. 30 epilepsy patients who had a seizure in the last 24 h, 30 epilepsy patients in remission, and 17 healthy controls were included in the study. The Human Orexin‐A Enzyme‐Linked Immunosorbent Assay Kit was used to measure serum orexin‐A level. In the ERG and CG, blood samples were obtained during routine controls. Results: No statistically significant difference was found between serum orexin levels of acute seizure group (ASG), epilepsy in remission group (ERG), and control group (CG). In the ASG, no significant difference was found when orexin levels were compared according to the time of blood sampling after seizure (0–8 h, 8–16 h, 16–24 h). In patients with seizures, the orexin levels of patients with focal seizures were compared with those of patients with generalized seizures. There was no statistically significant difference between the groups. Patients with seizures were evaluated according to electroencephalography (EEG) and cranial magnetic resonance imaging (MRI) findings, and no statistically significant difference was found between orexin levels between the groups. Conclusion: Our study is the first to evaluate orexin levels in children with epilepsy. Further research is needed to evaluate the role of orexins in the pathophysiology of epilepsy. With the clear relationship between orexin and epilepsy, antiorexinergic drugs can be used in the treatment of epilepsy.